Teacher Perception of students with Developmental Coordination Disorder (DCD) and school inclusion in Amazonas: preliminary data (Research, Society and Development, 2020)
Developmental Coordination Disorder (DCD) is a marked impairment in the development of motor coordination that affects performance in school activities. The teacher's perceptive view of this phenomenon may favor school inclusion. The objective of this work was to describe preliminary data on the teachers' perception regarding the academic performance of DCD students in Amazonas. The descriptive methodology was adopted through unstructured interviews and we performed the data analysis according to the Discursive Textual Analysis (DTA). Five teachers from a state school located in the south of the city of Manaus-AM participated in the interviews. The teachers were interviewed about students, in pairs, one with an indication of DCD and the other free of this condition, according to the motor assessment previously performed by the Laboratory of Studies in Human Motor Behavior - LECOMHpr. This article has as a preliminary conclusion that teachers perceive student’s school difficulties, but do not attribute them to the DCD phenomenon, a fact that brings us a reflection about how DCD negatively affects school life activities as well as the perception that teachers have about them. students, the school exclusion of this public suffers and the need to conduct further studies involving this phenomenon.